Print Publishing in America - Goldman, Judith; Stedelijk Museum Schiedam; Gemeentelijke van Reekumgalerij, Apeldoorn (Washington : United States International Communication Agency, 1980)
Albers, Josef ; Artschwager, Richard ; Bartlett, Jennifer ; Beal, Jack ; Bontecou, Lee ; Cage, John ; Close, Chuck ; Cornell, Joseph ; Crile, Susan ; Dine, Jim ; Estes, Richard ; Frankenthaler, Helen ; Graves, Nancy ; Grooms, Red ; Jacquette, Yvonne ; Johns, Jasper ; Katz, Alex ; Kelly, Ellsworth ; Lichtenstein, Roy ; Motherwell, Robert ; Nevelson, Louise ; Noland, Kenneth ; Oldenburg, Claes ; Pearlstein, Philip ; Porter, Fairfield ; Price, Ken ; Rauschenberg, Robert ; Rosenquist, James ; Ruscha, Edward ; Stella, Frank ; Tuttle, Richard ; Wiley, William T. ; Wujcik, Theo
Print Publishing in America, United States International Communication Agency, Washington, October 1979 - October 1980 (traveling exhibition), Stedelijk Museum Schiedam, 1 augustus - 8 september 1980 ; Gemeentelijke Van Reekum Galerij, Apeldoorn, 12 september - 15 october 1980
boek
Keywords: Amerika